2021
DOI: 10.1002/cctc.202101551
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Enhanced Activity of In Situ Formed Nanoparticles for Photocatalytic Hydrogen Evolution

Abstract: One consistent challenge of both computational and empirical catalyst screening is ensuring that the variables chosen for the screen are driving the performance analyzed. Here, we compare photocatalytic hydrogen evolution from in situ formed Au and Au/Cu nanoparticles to nanoparticles of the same composition synthesized prior to being used as catalysts, as well as compare them to in situ formed Au and Au/Cu nanoparticles in the presence of exogeneous ligand. For all experiments, we observed that ligand-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Previous work has indicated that an unprotected Pd colloidal cocatalyst at high enough concentration does not act as a sufficient catalyst due to agglomeration of the species and precipitation from solution. 51 PEGSH was introduced into these mixtures in equal concentration to the Pd salt in order to pacify the surface of the Pd colloids and extend the active lifespan of the cocatalyst. Results for the series of oxygenates under these conditions with and without a surface ligand can be seen in Figure 1, where oxalic acid, isopropanol, benzyl alcohol, and pyruvic acid demonstrated significant quantities of hydrogen evolution, and ethanol exhibits a small portion of H 2 produced under particular conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has indicated that an unprotected Pd colloidal cocatalyst at high enough concentration does not act as a sufficient catalyst due to agglomeration of the species and precipitation from solution. 51 PEGSH was introduced into these mixtures in equal concentration to the Pd salt in order to pacify the surface of the Pd colloids and extend the active lifespan of the cocatalyst. Results for the series of oxygenates under these conditions with and without a surface ligand can be seen in Figure 1, where oxalic acid, isopropanol, benzyl alcohol, and pyruvic acid demonstrated significant quantities of hydrogen evolution, and ethanol exhibits a small portion of H 2 produced under particular conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Utilizing our high-throughput reactor system, we were able to explore a variety of oxygenates at various concentrations of the Pd catalyst salt precursor with and without surface ligands, all within a single experiment. Previous work has indicated that an unprotected Pd colloidal cocatalyst at high enough concentration does not act as a sufficient catalyst due to agglomeration of the species and precipitation from solution . PEGSH was introduced into these mixtures in equal concentration to the Pd salt in order to pacify the surface of the Pd colloids and extend the active lifespan of the cocatalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Though LSPR-driven NP formations have now been studied for almost two decades, [11][12][13][14] few investigations have used molecular photochemistry, and specically photoreduction, to drive NP formation. [15][16][17][18][19] Yet using these strategies, such as molecular photosensitizers (PSs) to reduce metal ions, has several advantages, including the ability to control reaction outcomes via irradiation wavelength, intensity, and timing, as well as the photoredox properties of the PS, among other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54] They are also typically functionalized with small molecules and/or polymers that form a ligand shell around the NP core. 55 These ligand shells are critical for ensuring that the NPs remain colloidally stable, 56,57 and can impart desirable functionality to the NPs, such as stimuli responsiveness or specific sites for molecular recognition and/or targeting. 58 However, these ligands shells also increase the chemical and physical complexity of the NPs, especially in applications requiring mixtures of ligands with different sizes and functionalities.…”
Section: Introductionmentioning
confidence: 99%